Undetectable = Untransmittable: A Cross-Population Systematic Review and Meta-Analysis on Awareness and Acceptance - Nikolaos Georgiadis; Andreas Katsimpris; Perry N. Halkitis; Evridiki Kaba; Georgina Tzanakaki; Tonia Vassilakou; Apostolos Beloukas; Theodoros N. Sergentanis (Pathogens, 2025)
The Undetectable = Untransmittable (U=U) message is a cornerstone of HIV-related public health communication, yet global levels of awareness and acceptance remain unclear across key populations. This study aimed to assess the global prevalence of awareness and acceptance of the U=U message among men who have sex with men (MSM), people living with HIV (PLWH), healthcare professionals, and the general population. A systematic review and meta-analysis was conducted using data from PubMed, Embase, and Google Scholar without language restrictions through 31 October 2023. Eligible studies included prospective cohort studies, randomized clinical trials, and cross-sectional studies reporting numerical data on U=U awareness and acceptance. From 1171 screened records, 43 studies were included. Data were analyzed using a random effects model. The findings showed that U=U awareness was high among PLWH, moderate among MSM and healthcare professionals, and low in the general population. Complete acceptance of U=U was low in MSM and the general population, and moderate in PLWH and healthcare professionals. Any acceptance was moderate among MSM and the general population, and high among PLWH and healthcare professionals. These results highlight the need for targeted education strategies to enhance understanding and reduce HIV-related stigma, particularly in populations with lower awareness and acceptance.